Anti-histone H1 IgGs possess proliferative activity towards human T-leukaemia cem cells - Kit, Yu.; Magorivska, I.; Bilyi, R.; Myronovskij, S.; Stoika, R. (Experimental Oncology, 2017)
The aim of this study was to characterize the proliferative activity of the anti-histone H1 IgGs towards human T-leukaemia CEM cells. Materials and Methods: Anti-histone H1 IgGs were purified from blood serum of systemic lupus erythematosus patients by precipitation of serum proteins with 50% ammonium sulfate followed by a sequential affinity chromatography on Protein GSepharose and histone H1-Sepharose columns. To avoid contamination with other proteins, anti-histone H1 IgGs were subjected to strongly acidic pH 2.0 during gel filtration through HPLC column. The effects of the anti-histone H1 IgGs on cell viability and cell cycle were tested by MTS-assay and flow cytometry, correspondingly. The cross-reactivity of the anti-histone H1 antibodies towards heterogenetic and cellular antigens was evaluated by Western-blot analysis. Results: It was found that incubation of CEM cells with the HPLC-purified anti-histone H1 IgGs resulted in significant stimulation of cell growth by 46% after 48 h of incubation. These IgGs possess an antigenic poly-specificity to positively charged heterogenetic antigens and different cellular antigens. FITC-labeled and biotinylated anti-histone H1 IgGs are internalized by CEM cells and preferentially accumulated in the cytoplasm. Conclusion: The anti-histone H1 IgGs are shown to internalize human T-leukemia CEM and stimulate their proliferation. These IgGs are polyspecific toward cellular antigens.